Enhancing Pathogen Detection Methods through a Novel Molecular Diagnostic Approach with CRISPR/Cas Technology - Amanzholova, M.Zh.; Shaizadinova, А.М.; Abeldenov, S.К. (Fundamental and Experimental Biology, 2023)
Molecular diagnostics is widely recognized as one of the most efficient approaches for detecting and characterizing microorganisms. This method relies on the identification of specific nucleic acid sequences and enables the quick and precise determination of pathogen presence in various samples. Conventional methods for pathogen detection rely on the culture and identification of the pathogen in a laboratory setting, which can be time-consuming and expensive. Molecular diagnostic methods, such as PCR and DNA sequencing, have emerged as powerful alternatives to culture-based methods, offering greater sensitivity and specificity. However, these methods are still limited by their reliance on costly equipment and specialized expertise. In recent years, the CRISPR/Cas technology has emerged as a powerful tool for genome editing and manipulation, as well as for molecular diagnostics. This review presents a novel approach for improving pathogen detection methods through the utilization of CRISPR/Cas technology. The proposed method offers several distinct advantages over existing molecular diagnostic techniques. Notably, it provides enhanced specificity and accuracy, thereby minimizing the occurrence of false-positive results. Additionally, this method can rapidly and effectively detect pathogens, making it particularly attractive for use in clinical and laboratory settings. Therefore, molecular diagnostics using CRISPR diagnostics based on Cas12a is a powerful tool for pathogen detection and improving the accuracy and speed of diagnosis. Its prospects for future use are wide-ranging and may encompass many areas of life sciences.